(untitled) (Philological Studies, 2019)
In the mythical structure characters and conflicts also arise from the basic opposition man’s world versus higher power as the hero has a peculiar cultural position of mediator. Literary heroes, regardless of genre and stylistic formation, are realized and recognized in several semantic levels, with their typical traits and characterization establishing various relations towards category of national, religious, social or gender identity. Character-symbol grows, absorbs these components, and is recognized in every community in the same way. The creation and reception of epic folk songs require an emotional engagement of both singer and audience. The primary signal – nomenclature already suggest features of “his” and “others” cultures. This paper will point out the various processes of shaping an epic hero, whose characteristics are caused by a wider social context (time and place of improvisation). The most frequent consequences of “moving” a hero from his cultural zone / environment (absolute antagonism – his own : his own, his own: others; antipodes; partial adaptation; adoption) will be allocated from the corpus of epic poems coming from the South Slavic area.